Growth and Yield of Lettuce (Lactuca sativa L.) by Giving Cow Manure and Empty Palm Oil Bunch Fertilizer on Peat Soil - Manullang, Yedija; Herawati, Reny; Handajaningsih, Merakati; Ganefianti, Dwi Wahyuni; Haquarsum, Eka J.V.; Sutrawati, Mimi (Akta Agrosia, 2020)
Lettuce (Lactuca sativa L.) is a horticultural plant that is beneficial for health. Efforts are being made to expand the plant area. One of them is by utilizing marginal land such as peatlands.  Peatlands in Indonesia are the most extensive soils in various tropical countries in the world that have low soil fertility and high acidity so that they are not optimal for lettuce growth. The provision of organic material can increase soil fertility by improving physical, chemical, and biological soil properties so that it can support lettuce growth. This study aims to determine the dose of cow manure and the dosage of oil palm empty fruit bunch fertilizer and the optimal dose interaction for growth and yield of lettuce. This research was conducted from June 2019 to August 2019 in Bengkulu City. This study uses a Completely Randomized Design consisting of two factors, which are repeated three times. The first factor is the dose of cow manure with three levels, namely: 0 tons ha-1, 15 tons ha-1, and 30 tons ha-1. The second factor is the dose of oil palm empty fruit bunch fertilizer, which consists of four levels, namely 0 tons ha-1, 5 tons ha-1, 10 tons ha-1, and 15 tons ha-1. The results showed that the dosage of cow manure 15 tons ha-1 and without the application of empty fruit bunches fertilizer gave the best results in leaf length of 18.674 cm. The best dose of cow manure for growth and yield of lettuce is 15 ha-1. The application of OPEFB fertilizer has not been shown to affect the growth and yield of lettuce.